#TITLE_ALTERNATIVE# - PRAMONO (NIM: 22015023), WAHYU
The Peciko is a gas field in Mahakam Delta which was discovered in 1991 and started to produce gas in 1999. The gas production in this field is derived from multilayer reservoirs accumulated in four ways NE-SW gentle anticline structure. High resources of gas accumulation is controlled by the combination of structure, stratigraphic and hydrodynamic trap. The study of overpressure controlling gas accumulation is performed to investigate additional resource and anticipating declining of production rate in the field. The overpressure originated from the southern area causes gas accumulation to shift from structural crest to cause tilted gas water contact. This circumstance controls gas accumulation, i.e. the deeper the reservoir, the greater the overpressure, the further the gas accumulation shifts from the crest. The evaluation of pressure control to gas accumulation is performed by normalizing the gas water contact. The maximum pressure value in each layer, and normal crest to hydrodynamic crest movement distance are measured to observe pressure effect to gas accumulation distance from the crest and the shifting of the gas accumulation. The gas acummulation of 6 evaluated layers shows the accumulation shifting is increasing with increasing depth. In slightly overpressured layers (1h, 2a and 3a), gas is located in the flank due to presence of small pressure difference. In the overpressured layers (4a, 4f, and 4i), gas accumulation are located further away from the crest due to high pressure difference. By using the equation obtained from overlying layers, gas accumulation in the Deep Peciko prospect is expected to be located at the distance of 5-8-11km from the crest of anticline.